PENGARUH MODEL PEMBELAJARAN DAN GAYA BERPIKIR TERHADAP PEMAHAMAN NILAI-NILAI MULTIKULTURAL SISWA PADA PEMBELAJARAN PAI DI SMK NEGERI 2 KOTA BENGKULU - zaleka, zaleka; Dewi, Desy Eka Citra; nurlaili, nurlaili (UIN Fatmawati Sukarno Bengkulu, 2021)
The objectives of the study are: (1) To analyze the magnitude of the influence of learning models on students' understanding of multicultural values in PAI learning at State Vocational High School 2 Bengkulu City. (2) To analyze the magnitude of the influence of thinking styles on students' understanding of multicultural values in PAI learning at State Vocational High School 2 Bengkulu City. (3) Analyze the magnitude of the influence of learning models and thinking styles on students' understanding of multicultural values in Islamic Religious Education learning at SMK Negeri 2 Bengkulu City. . The type of quantitative research with an associative approach, the data collection technique is a questionnaire, the data analysis technique used is descriptive statistics, basic assumption tests, classical assumption tests, and hypothesis tests using simple linear regression and multiple linear regression, t-test and F-test, population and sample of 70 students. Research results (1) There is an influence of the learning model as indicated by the coefficient value of X1Y equal to 0.593 using the t-test, then the calculated t is 5.640> t table (5% = 1.69), and at a significance level of 0.000 t table (5% = 1.69) and at a significant level of 0.007 F table (5% = 2.85) and at a significance level of 0.032